Republic of Belarus : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2017)
The paper considers the relatively low level of diversification of Belarusian exports relative to peers, and barriers to higher export potential. Belarus faces different trade regimes vis-a-vis its largest trading partner, Russia, in the framework of the Eurasian Economic Union (EEU); and its second-largest, the European Union (EU). The paper discusses tariff and nontariff barriers within the EEU; the more restrictive trade relations with the EU; and other potential barriers to trade, including logistics and limited trade facilitation. WTO accession would help improve export competitiveness. Further EEU integration could also boost trade potential, but with the attendant risk that trading links become more concentrated rather than diversified. Belarus's largest revealed comparative advantages are in areas where it is difficult to move into new products. Belarus's trade patterns are significantly more concentrated than those of peer countries. Belarus has lowered tariffs in recent years, including in the framework of the Eurasian Economic Union (EEU).